2001
DOI: 10.1093/carcin/22.4.593
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in DNA repair genes and risk of lung cancer

Abstract: Polymorphisms in DNA repair genes may be associated with differences in the repair efficiency of DNA damage and may influence an individual's risk of lung cancer. The frequencies of several amino acid substitutions in XRCC1 (Arg194Trp, Arg280His and Arg399Gln), XRCC3 (Thr241Met), XPD (Ile199Met, His201Tyr, Asp312Asn and Lys751Gln) and XPF (Pro379Ser) genes were studied in 96 non-small-cell lung cancer (NSCLC) cases and in 96 healthy controls matched for age, gender and cigarette smoking. The XPD codon 312 Asp/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
181
5
2

Year Published

2002
2002
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(208 citation statements)
references
References 25 publications
20
181
5
2
Order By: Relevance
“…6,7 In our population, the XRCC1-194Trp variant allele was rare (0.09). The XPD-751Gln variant allele occurred with a frequency of 0.47, which is slightly higher than that reported in lung cancer patients by Spitz et al 9 and by Butkiewicz et al, 6 but compatible with that reported by David-Beabes et al 18 The XPD-312Asn variant allele frequency (0.42) was similar to that of Butkiewicz et al 6 but higher than that given by Spitz et al 9 The polymorphisms in codons 312 and 751 of the XPD gene appeared to be in linkage disequilibrium in our study ( 2 34.85; p Յ 0.001), consistent with recent reports. 6,9 Thirty-four patients (56.6%) were GSTM1 null genotype, which results from the total absence of the gene.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…6,7 In our population, the XRCC1-194Trp variant allele was rare (0.09). The XPD-751Gln variant allele occurred with a frequency of 0.47, which is slightly higher than that reported in lung cancer patients by Spitz et al 9 and by Butkiewicz et al, 6 but compatible with that reported by David-Beabes et al 18 The XPD-312Asn variant allele frequency (0.42) was similar to that of Butkiewicz et al 6 but higher than that given by Spitz et al 9 The polymorphisms in codons 312 and 751 of the XPD gene appeared to be in linkage disequilibrium in our study ( 2 34.85; p Յ 0.001), consistent with recent reports. 6,9 Thirty-four patients (56.6%) were GSTM1 null genotype, which results from the total absence of the gene.…”
Section: Resultsmentioning
confidence: 76%
“…6,8,9,18,24 Since peripheral blood DNA adducts have been reported to be possibly predictive of lung cancer risk, 25 many recent studies evaluated the possible effect of DNA repair polymorphisms on DNA damage, mainly by detecting unspecific bulky DNA adducts by 32 P-postlabelling techniques. 26 -29 Given the nature of this method, the exact composition of adducts is usually unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In another case-control study of 124 bladder cancer cases and 85 controls with benign diseases in Italy, Matullo et al 27 found a statistically significant association between the C18067T polymorphism and risk of bladder cancer, particularly among those with the slow acetylator genotype (ORϭ3.4, 95% CIϭ1.5-7.9) and among nonsmokers (ORϭ4.8, 95% CIϭ1.1-21.2). However, the XRCC3 18067T variant was not significantly associated with risk of lung cancer in a smaller hospital-based case-control study (96 lung cancer cases and 96 controls) in a Polish population, 29 and in another larger populationbased case-control study (178 lung cancer cases and 453 controls) of U.S. Caucasians, 30 but the authors did not present their stratification analysis in subgroups such as gender, which may partly due to the small number of cases included in both studies. 29,30 We observed a significantly elevated risk in current smokers, suggesting that there may be gene-environment interaction in the development of SCCHN.…”
Section: Resultsmentioning
confidence: 81%
“…However, the XRCC3 18067T variant was not significantly associated with risk of lung cancer in a smaller hospital-based case-control study (96 lung cancer cases and 96 controls) in a Polish population, 29 and in another larger populationbased case-control study (178 lung cancer cases and 453 controls) of U.S. Caucasians, 30 but the authors did not present their stratification analysis in subgroups such as gender, which may partly due to the small number of cases included in both studies. 29,30 We observed a significantly elevated risk in current smokers, suggesting that there may be gene-environment interaction in the development of SCCHN. Recently, Matullo et al reported a significant association between formation of bulky DNA adducts in white blood cells and the XRCC3 18067TT and 18067CT genotypes not only in 124 bladder cancer patients 27 but also in 308 healthy individuals.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation